The challenge of teacher training through internet: a Portuguese example and international reflection - Davis, Niki (2012)
As the twentieth century draws to a close there appears to be a consensus that teacher training can be delivered virtually using the Internet. Three EC funded international projects (T3, REM and TRENDS) have demonstrated that this is practical and there are other examples around the world. However, such-modes of teacher training are challenging and appear to require considerable re-engineering of educational processes as well as information and communication technologies. This paper discusses these challenges by focussing on the experience of a group of Portuguese student teachers and their tutor within the multinational EUMedea course. The EUMedea Project was a teacher training on-line course of the T3 Project Telematics for Teacher Training about ‘Environmental Education’. It involved 11 groups of teachers/student teachers from five European countries: United Kingdom, Portugal, Italy, Finland and Holland. The aims of the course were: to designing environmental education project; use Internet to find information, share knowledge and co-operate in designing environmental education projects; use a Computer Mediated Communication (CMC) environment to work with other teachers co-operatively. This paper will present the results, discussions and reflections of the group of Castelo Branco (Portugal). The results of this experimental course will be an opportunity to reflect and propose several insights and clues for the future use of Internet on teacher training.